Freelance вЂ” Freedom вЂњfromвЂќ or вЂњforвЂќ? Book Review: Shevchuk A.V. Chto my znaem o frilanserakh? Sotsiologiya svobodnoi zanyatosti. [What do we know about Freelancers? Sociology of Free Employment]. Moscow: Izd. dom вЂњVysshei shkoly ekonomikiвЂќ publ., 2022 - Anita A. Poplavskaya (Социологический журнал, 2023)
The new book by Denis Strebkov and Andrey Shevchuk “What do we know about freelancers? The Sociology of Free Employment” (2022) is a summation of a unique, large-scale, more than a decade-long research project dedicated to understanding the phenomenon of online freelancing. The authors are at the forefront of surveying free employment agents in the country. They describe the history of the formation of the Russian-speaking remote work market, its main participants and the laws by which it functions, while also conducting deep analysis of the origin, spread and transformation of remote self-employment practices and the composition of workers in this realm of labor. Freelancers are defined by the authors of the monograph as people who partake in intellectual and creative work, and freelancing itself is characterized as a sort of embodiment of freedom in the labor market. The title of the book suggests a new area of research — sociology of free employment. The review considers the merits of the monograph, while posing the question of whether we can even assert that independent professionals are truly free, or if there are certain caveats to it.